Measurement and Data Science. - Péceli, Gábor (Cambridge Scholars Publisher, 2021)
Nowadays, all of us enjoy the worldwide revival of measurement and data science caused by the revolution of sensory devices and the amazing data transmission, storage and processing capabilities available and embedded everywhere. Thanks to the unbelievable amount of recorded information and the theoretical results of measurement and data science, a great deal of newly developed products invade our surroundings and enable previously unconceivable smart services and support.This volume consists of a number of chapters covering the scientific results of researchers working in this field at the De.